Application of the Floyd Warshall Algorithm in Determining the Shortest Route for Distribution of UD Nadira Cinta Rasa Bread to Praya, Central Lombok - Annisa Zaen Febryantika; Fidyatnisa Alyunda Puspandini; Indah Rizqiana Amalia; Maya Annisa (University of Mataram, 2021)
Optimizing the shortest route is needed by a company in the process of distributing goods to consumers. This optimization can help companies optimize the mileage and costs from source to destination. In this study, the shortest route method used is the Floyd-Warshall algorithm to determine the shortest route. Floyd-Warshall algorithm can compare all the possible paths in the graph for each side of all vertices it passes with the minimum number. Based on the calculation results of this study, the shortest route was obtained from Mataram as the source and Praya as the destination was 31 km.